Main-chain benzoxazine precursor block copolymers. Issue 2 (7th December 2017) - Deliballi, Zeynep; Kiskan, Baris; Yagci, Yusuf
Abstract : A novel strategy for one-pot preparation of block copolymers of benzoxazine precursors with polyetheramines is described. Abstract : A novel strategy for the preparation of block copolymers of polymeric benzoxazine precursors with polyetheramines by one-pot two-step or stepwise pathways is described. The method pertains to the use of simple chemicals such as 4-hydroxyaniline, formaldehyde and polyetheramines (Jeffamines). The structures and molecular weights of the polymers were characterized by FTIR, 1 H NMR, and GPC. Successful block copolymer formation was evidenced by the clear shift of the molecular weight of the block copolymer to the higher molecular weight region. Thermal properties of the polymers were also investigated by using DSC and TGA. Block copolymers were shown to undergo thermally activated curing by the ring-opening polymerization of the benzoxazine block. The thermal stability of the cured product drastically increased compared to the precursor polyetheramine.